Ventral prefrontal cortex is not essential for working memory. - Rushworth, M; Nixon, P; Eacott, M; Passingham, R (1997)
It is widely held that the prefrontal cortex is important for working memory. It has been suggested that the inferior convexity (IC) may play a special role in working memory for form and color (). We have therefore assessed the ability of monkeys with IC lesions to perform visual pattern association tasks and color-matching tasks, both with and without delay. In experiment 1, six monkeys were trained on a visual association task with delays of up to 2 sec. Conservative IC lesions that removed lateral area 47/12 in three animals had no effect on the task. Further experiments showed that these lesions had no effect on the postoperative new learning of a color-matching task with delays of up to 2 sec or versions of the visual association task involving delays of up to 8 sec. In experiment 2, larger lesions of both areas 47/12 and 45A were made in the three control animals. This lesion caused a profound deficit in the ability to relearn simultaneous color matching, but subsequent matching with delays of up to 8 sec was clearly unimpaired. We suggest that the IC may be more important for stimulus selection and attention as opposed to working memory.